Respostas
respondido por:
0
Olá!!!
Resolução!!!
= ( - 9 ) - ( + 7 ) + ( + 13 ) - ( - 20 )
= - 9 - 7 + 13 + 20
= - 9 + 6 + 20
= - 3 + 20
= + 17
Espero ter ajudado!!!
Resolução!!!
= ( - 9 ) - ( + 7 ) + ( + 13 ) - ( - 20 )
= - 9 - 7 + 13 + 20
= - 9 + 6 + 20
= - 3 + 20
= + 17
Espero ter ajudado!!!
respondido por:
0
Resposta:
17
Explicação passo-a-passo:
(-9)-(+7)+(+13)-(-20)
- 9 - 7 + 13 + 20
- 16 + 33
+ 17
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás